In situ growth of Pt3Ni nanoparticles on an A-site deficient perovskite with enhanced activity for the oxygen reduction reaction. Issue 14 (21st March 2017) - Gao, Yang; Wang, Jian; Lyu, Yu-Qi; Lam, Kwunyu; Ciucci, Francesco
Abstract : A perovskite material with in situ exsolved Pt3 Ni nanoparticles is applied for oxygen reduction reaction catalysis with dramatically improved activity. Abstract : A novel A-site deficient perovskite, La0.9 Mn0.9 Pt0.075 Ni0.025 O3− δ, is developed as a catalyst for the oxygen reduction reaction in alkaline solution. Pt3 Ni nanoparticles are exsolved in situ on the surface upon reduction. The catalytic activity improves significantly after exsolution. This improvement is attributed to the synergy between the host perovskite and the nanoparticles.